Temperature-insensitive displacement sensor based on high-birefringence photonic crystal fiber loop mirror - Zhang, Hao; Liu, Bo; Wang, Zhi; Luo, Jianhua; Wang, Shuangxia; Jia, Chenglai; Ma, Xiurong (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
A temperature-insensitive displacement sensor based on high-birefringence photonic crystal fiber loop mirror (Hi-Bi PCFLM) is proposed. Through the measurement of transmission peak wavelength of the Hi-Bi PCFLM, this displacement sensor quantifies the free end displacement of a uniform-strength cantilever beam, on which part of Hi-Bi PCF is pasted. We have theoretically analyzed its operation principle, which is validated by our experimental results. This displacement sensor has the sensitivity of 0.28286 nm/mm and 0.27024 nm/mm over a range from –21 mm to 21 mm for two adjacent peak wavelengths, respectively. Experimental observation indicates that this sensor has good stability through a temperature range from 40 °C to 109.5 °C.
Optica Applicata, Vol. 40, 2010, nr 1, s. 209-217
Keywords: optyka; fiber-optic sensor; displacement sensor; high-birefringence fiber loop mirror (Hi-Bi FLM); photonic crystal fiber (PCF); uniform-strength cantilever beam (UCB)